Teaching writing strategies to middle school students with disabilities - Monroe, Brandon W.; Troia, Gary A. (Journal of Educational Research, 2006)
Following less than 8 hr of instruction in the use of strategies to facilitate planning, self-regulation, and revising while writing opinion essays, a group of 3 middle school students with learning disabilities (LD) made substantial gains in each of 5 quality traits on which their papers were scored. On average, posttest scores of students with LD were better by 1 point on a 6-point scale than were those scores obtained by a group of LD students who served as controls. Participants' scores approached the level of writing performance exhibited by a group of peers without disabilities. The authors also observed treatment effects for number of functional essay elements; students who received strategy instruction gained an average of 1.3 functional elements from pretest to posttest. However, generalization to narrative writing was not obtained.
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/088-325-822-977-127 tex.unique-id: [object Object]
Keywords: Effects on writing quality; Middle school students with learning disabilities; Strategies for supporting the writing process; dept.rdg